Interrelationship between the Use of New Agricultural Inputs and Socio-economic Factors - Wagle, Shyam Prasad (Journal of Research and Development, 2022)
This paper deals with interrelationship between the use of new agricultural technology and socio-economic factors in Dhankuta municipality, eastern hills of Nepal. This area offers a lot of resources; here the researcher examines the role of socio-economic factors to diffuse new technology in this area too. Relevant data were obtained from both primary and secondary sources. Primary data were collected from the interview, key informant survey and field observation. For this, approximately 33 percent sample households (166hhs) were selected out of total 506 households from ward no. 3 of the municipality. Similarly, secondary data were gathered from various books, journals and official records. To identify the mutual relationship between these components, mathematical tools chi-square test and Karl Pearson's correlation were performed. The study reveals that there is a close relationship between the use of new agricultural inputs and socio-economic factors of the study area. The relationship seems highly significant between age, training, farm size, service of agriculture service center and membership of farmers in organization and adoption of new agricultural technologies however; the inter-connection with sex, ethnicity and education of the farmers reveals less significant among these factors. Nowadays, more than 78 percent (130hhs) farmers are using such inputs in the study area and the remarkable change in crop production can easily be seen due to the impact such innovations.